Chitosan nanoparticle-based delivery of fused NKG2D–IL-21 gene suppresses colon cancer growth in mice - Tan L (Dove Medical Press, 2017)
Lunmei Tan,1 Sen Han,2 Shizhen Ding,2 Weiming Xiao,3,4 Yanbing Ding,3 Li Qian,2,4 Chenming Wang,1,5 Weijuan Gong1–5 1Jiangsu Co-innovation Center for Prevention and Control of Important Animal Infectious Diseases and Zoonoses, 2Department of Immunology, School of Medicine, 3Department of Gastroenterology, The Second Clinical Medical College, 4Department of Integrated Chinese and Western Medicine, School of Medicine, 5Jiangsu Key Laboratory of Zoonosis, Yangzhou University, Yangzhou, People’s Republic of China Abstract: Nanoparticles can be loaded with exogenous DNA for the potential expression of cytokines with immune-stimulatory function. NKG2D identifies major histocompatibility complex class I chain-related protein in human and retinoic acid early induced transcript-1 in mouse, which acts as tumor-associated antigens. Biologic agents based on interleukin 21 (IL-21) have displayed antitumor activities through lymphocyte activation. The NKG2D–IL-21 fusion protein theoretically identifies tumor cells through NKG2D moiety and activates T cells through IL-21 moiety. In this study, double-gene fragments that encode the extracellular domains of NKG2D and IL-21 genes were connected and then inserted into the pcDNA3.1(–) plasmid. PcDNA3.1–dsNKG2D–IL-21 plasmid nanoparticles based on chitosan were generated. Tumor cells pretransfected with dsNKG2D–IL-21 gene nanoparticles can activate natural killer (NK) and CD8+ T cells in vitro. Serum IL-21 levels were enhanced in mice intramuscularly injected with the gene nanoparticles. DsNKG2D–IL-21 gene nanoparticles accumulated in tumor tissues after being intravenously injected for ~4–24 h. Treatment of dsNKG2D–IL-21 gene nanoparticles also retarded tumor growth and elongated the life span of tumor-bearing mice by activating NK and T cells in vivo. Thus, the dsNKG2D–IL-21 gene nanoparticles exerted efficient antitumor activities and would be potentially used for tumor therapy. Keywords: NKG2D, IL-21, fusion gene, cancer, chitosan nanoparticle